MOLECULAR MARKERS: IMPLEMENTATION IN CROP PLANT BREEDING FOR IDENTIFICATION, INTROGRESSION, AND GENE PYRAMIDING - I. N. Leonova (Вавиловский журнал генетики и селекции)
Over the past decades, wide theoretical and practical experience has been obtained in application of DNA markers for investigation of plant genetic diversity, construction of molecular genetic maps, mapping of genes and quantitative trait loci, and employment of molecular marker technologies in the development of commercial cultivars and breeding of crop lines. To date, the main practical application of molecular markers is related to germplasm characterization, introgression and pyramiding of genome fragments associated with agronomically important traits controlled by major genes. The contribution of new technologies to the selection of traits with multigenic inheritance is still insignificant. Despite the considerable progress in plant molecular genetics and genomics methods and great interest in new technologies among breeders, there is a large number of constraints affecting the implementation of new technologies in practical selection. This article considers the potential application of DNA markers in breeding of crop plants and the benefits and limitations of use of marker-assisted technologies in comparison with conventional plant breeding methods.